Islamic Law on companies and corporations - Mohamed Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan; Masum, Ahmad (Sweet & Maxwell, Thomson Reuters, 2025)
Company is called in Arabic as “Shirkah” and it means “join together” and defined as a contract between partners in capital and profits. It can be elaborated further as the participation of two or more persons in a certain business with defined amounts of capital in accordance with a contract for carrying out a business together and for sharing profit and loss. This concept was recognised from the inception of Islam and this is considered as a useful method to shape the business relation. Meanwhile, under conventional law, the corporation is considered a popular business vehicle in the current environment. It is an artificial person or legal entity created by or under the authority of the laws of a state. It is an association of persons created by statute as a legal entity which is treated by law as a person that can sue and be sued. Further, it is distinct from the individuals who establish it. The death of an investor does not impact its existence as shares can usually be transferred; and have a personality and existence distinct from that of its several members. The aim of a corporation is either to carry out a business for profit or to provide a service. As a corporation is an artificial person, it requires some form of aql (intellect) to perform its business. This brain or decision- making power can be entrusted to an individual, or a group of individuals, such as the board of directors. A corporation can own a property in its name. It can engage in business, incur liabilities and can sue to protect its interests and be sued by others too. Like an individual, it has all rights and privileges subject to the limitations imposed by the laws of a country. Banks, credit unions, investment trust companies, cooperatives, etc. are good examples of different forms of corporations. Every corporation has the same legal rights under the company law as a human, and it can take original ownership of the property, enter into contracts, sue and be sued, all in its name, separate and distinct from its partners. Therefore, the legal position of the incorporated company is straightforward.